Kudus Kulon as a living heritage site: The dialectics of heritage preservation - Astari Wulandari; Atik Suprapti; Agung Budi Sardjono (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This study aims to determine the characteristics of continuity in the Kudus Kulon living heritage site. Furthermore, this study seeks to explain the process of cultural heritage preservation through the lens of spatial production, which involves the collaboration of various actors. This research is expected to provide deeper understanding of studies on living heritage and spatial production, as well as provide practical contributions to strengthening community-based preservation strategies in living heritage site. Methods: This research uses a qualitative approach with a case study strategy to understand cultural heritage preservation in Kudus Kulon as a living heritage site. Data were obtained through field observations, in-depth interviews, and documentation studies, then analyzed thematically using the living heritage framework and Lefebvre's theory of spatial production. The analysis was conducted to identify forms of continuity, community practices, and the reproduction of spatial meaning in the cultural heritage preservation process. Findings: These research findings confirm and enrich the Western concept of living heritage by highlighting the continuity of original functions, transformation, the involvement of core communities, and sustained adaptability. The Sunan Kudus Heritage site, the traditional Joglo Pencu house, and the Buka Luwur and Dandangan traditions demonstrate that heritage remains alive not by being frozen in time, but through continuous use, maintenance, and reinterpretation by the community and local foundations. In this context, social change and institutional adjustments do not weaken the heritage; rather, they become integral to the sustainability strategy of the heritage space. Conclusion: Kudus Kulon demonstrates its capacity as a dialectical space of living heritage, where continuity and change do not negate each other, but rather complement each other within a unique and contextual framework of socio-spatial relations. Novelty/Originality of this article: This study offers a novel contribution by integrating the